Optimasi Adsorpsi Ion Cd2+ Pada Silika Gel – GPTMS (glisidoksilpropoltrimetoksisilan) Termodifikasi Sulfonat - Pebriani, Pebriani; Oktavia, Budhi; Nasra, Edi; Riga, Riga (Periodic, 2024)
Adsorbents that are often used in the adsorption process are silica gels. Silica gel has unique advantages such as being, having ion exchange ability, being stable at high temperatures, not floating on organic solvents, and being easy to modify. But the effectiveness of silica gel adsorption against metal ions is weak, so it needs to be modified on the surface of silica gel. The modifier used is a sulfonate group derived from a 4-amino-5-hydroxy-2,7-naphthalenedisulfonate salt using a glycosidoxypropyltrimethoxysilane linkage (GPTMS). The purpose of this study is to determine the optimum conditions for the Cd2+ ion with variations in pH and contact time. The results of the study obtained optimal conditions for the absorption of the Cd2+ ion at pH 5 and a contact time of 60 minutes.